Extending Minsky's classifications of fragility to government and the open economy - L. Randall Wray (Levy Economics Institute of Bard College, 2006)
Minsky's classification of fragility according to hedge, speculative, and Ponzi positions is well-known. He wrote about fragile positions of individual firms and of the economy as a whole, with the economy transitioning naturally from a robust financial structure (dominated by hedge units) to a fragile structure (dominated by speculative units). In most of Minsky's writing, he introduced government through its impact on the private sector with its spending and balance sheet operations as stabilizing forces (although he insisted that stability is ultimately destabilizing). On a few occasions he also analyzed the government's own balance sheet position. More rarely, Minsky extended his analysis to the open economy, examining the fragility of external debt positions. In these works, he analyzed the United States as the world's bank and discussed the impact of various U.S. balance sheet positions on the rest of the world. This paper will carefully examine Minsky's position on these topics, and will offer an extension of Minsky's work. It will also examine the sustainability of the current twin U.S. deficits.
Keywords: E32; E42; E62; F4; G15; 330; Hyman Minsky; financial fragility; financial instability hypothesis; current account deficit; budget deficit